Infraspecific Variation of Bambusa nutans Subspecies Nutans from Six Different Sites of Central Nepal - Adhikari, Ramesh; Shrestha, Keshab (Scientific World, 2010)
Bambusa nutans Wallich ex Munro subspecies nutans is a valuable economic plant occurring especially on the Terai region and mid hills (Kathmandu valley) in Nepal from sea level to 1700 m. Variation plays major role to compare the populations and to select superior trees for breeding purpose. Infraspecific variation is the study of comparison between plants belonging to the same species but from different populations which could be distinguished in nature. Study on the infraspecific variation of this species has been carried out from six different stands (Kapan, Kirtipur, Sisneri, Naldum, Kafledi and Narayanghat) of Central Nepal ranging in altitude (from 256 m to 1850 m) and climatic conditions. Altogether 10 culms, from 3-4 clumps were selected and 6 morphological characters having utmost importance in bamboo growth has been studied. Those characters were culm height, culm diameter at breast height, culm wall thickness, internode length ,culm sheath length and culm sheath breadth. Statistical analysis was performed for the calculation of correlation coefficient using SPSS software program. Variation within and among population was analyzed using one way ANOVA. All the characters show significant differences with 5% level of significance and ratios of morphological characters also show the significant differences except CH/CD, which was not significant. From the present study it is concluded that significant differences were observed in phenotypic characters. Since genetic differences leads to the variation among the plants, these variations might be of genetic origin .Reciprocal transplant experiment and progeny testing should be conducted for further research. Provided information can be utilized to conserve the genetic resources and to exploit these resources scientifically and economically. Keywords: Bambusa nutans subspecies nutans; Infraspecific variation; Correlation; ANOVA; Genetic differences. DOI: 10.3126/sw.v6i6.2639 Scientific World, Vol. 6, No. 6, July 2008 81-84